Delineating the social valuation network in adolescents. Issue 11 (4th November 2019) - Kumar, Poornima; Pisoni, Angela; Bondy, Erin; Kremens, Rebecca; Singleton, Paris; Pizzagalli, Diego A; Auerbach, Randy P
Abstract: Adolescents strive for peer approval, and an increased sensitivity to peers' opinions is normative. However, among vulnerable adolescents, peer evaluation can be detrimental, contributing to affective disorders. It is, therefore, critical to improve our understanding of neural underpinnings of peer evaluation. Prior research has investigated averaged neural responses to peer acceptance or rejection, neglecting to probe trial-by-trial computations that mirror real-time updating of daily activities. In non-social decision-making, a common neural valuation system centered on the medial prefrontal cortex (mPFC) has emerged, which evaluates different reward types on a common scale to guide choices. However, it is unclear whether the mPFC also tracks complex social scenarios involving peer feedback. To address this gap, we acquired fMRI data from 55 healthy adolescents during the Chatroom Task, which probes peer evaluation, and implemented a computational approach to characterize trial-by-trial social value, thereby allowing us to interrogate the neural correlates of social value. Consistent with our hypothesis, social value signals were encoded in the mPFC. Interestingly, analyses also revealed a wider social-specific valuation network including the precuneus and amygdala. Understanding how adolescents make social decisions and neural markers associated with it, may, ultimately, help us clarify promising targets for intervention.